(untitled) (ҚазҰУ Хабаршысы. География сериясы, 2023)
Based on the analysis of the current development state of the tourism development in Aksu-Zhabagly Biosphere Reserve (BR), this paper discusses how to properly handle the contradiction between nature protection and tourism development, determines the problems existing in tourism development, and proposes a strategy for the development of eco-tourism in Kazakhstan. The aim of the study is to give some recommendations for the Aksu-Zhabgly ecotourism destination by employing a combination of field observation, examination, evaluation, and SWOT analysis. The strategic suggestions for the future development of tourism in Aksu-Zhabagly BR were determined mainly by the SWOT analysis results. The study results showed that the main strengths are convenient accessibility, diversified wild animals and plants, rich natural values, tranquil life in a typical rural setting, and favorable climatic conditions in the summer. And the low quality of tourist services, lack of competition among tourist destinations, lack of necessary infrastructure for tourists, lack of investment capital for tourism development, and lack of access to credit for small business development were determined as the main weakness. The results also revealed the preparation of different types of tour packages, the development of community tourism groups in Zhabagly, the potential for the production and sale of folk crafts and souvenirs, and improving accessibility (rehabilitation of roads, public transport) are the main opportunities. Finally, the hazards of increased influx of tourists, monopolization of tourist revenues and uncontrolled development of tourism, unlimited use of social opportunities and natural resources, loss of newly acquired image through the supply of low-quality goods, and the inability of other neighboring settlements to compete with Zhabagly village were proved to be the main threat to the effective implementation of sustainable development of tourism in the Aksu-Zhabagly tourist site.